2007
DOI: 10.1007/s00428-007-0482-8
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–mesenchymal transition (EMT) of renal tubular cells in canine glomerulonephritis

Abstract: Tubulo-interstitial fibrosis in dogs may result from primary injury to the interstitium or develop secondary to other renal diseases. As in human renal pathology, tubular epithelial cells (TEC) are believed to actively participate in the mechanisms of renal fibrosis. In this study, we examined the changes in the tubular epithelial component in two specific canine diseases. Immunohistochemistry showed the expression of the epithelial marker cytokeratin, the smooth muscle marker alpha-SMA, the mesenchymal marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
1
23
2
Order By: Relevance
“…We found that the TIMP-1 directly regulated transformation of fibroblasts into myofibroblasts, evident from the examination on α-SMA and TGFβ1 levels. α-SMA is specific marker for myofibroblasts, and is not express by normal fibroblast [24][25][26][27]. The EMT is a process by which epithelial cells acquire a migratory, mesenchymal phenotype, as a result of its repression of E-cadherin [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the TIMP-1 directly regulated transformation of fibroblasts into myofibroblasts, evident from the examination on α-SMA and TGFβ1 levels. α-SMA is specific marker for myofibroblasts, and is not express by normal fibroblast [24][25][26][27]. The EMT is a process by which epithelial cells acquire a migratory, mesenchymal phenotype, as a result of its repression of E-cadherin [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Although the origin of myofibroblasts has not yet been clearly elucidated, results from numerous studies indicate that a large number of myofibroblasts arise through a mechanism of epithelial-mesenchymal transition [1,2,3,4]. …”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indicates that tubular epithelial cells are capable of transforming into myofibroblasts under pathological conditions; this process is called tubular epithelial cell-myofibroblast transdifferentiation (TEMT). A number of studies have demonstrated evidence of TEMT [1,2,3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…In normal canine kidneys, the visceral glomerular epithelial cells (podocytes) expressed only vimentin, and cytokeratin was found exclusively in parietal glomerular epithelial cells. Aresu et al [27] showed that in dogs' kidneys, epithelial tubular cells lose their cytokeratin staining characteristics and transdifferentiate into cells exhibiting a key mesenchymal feature of vimentin-positive staining in glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%